Cognitive Resilience to Apolipoprotein E ε4: Contributing Factors in Black and White Older Adults - Kaup, Allison R. (JAMA Neurol, 2015)
IMPORTANCE: Apolipoprotein E (APOE) ε4 is an established risk factor for cognitive decline and the development of dementia, but other factors may help to minimize its effects. OBJECTIVE: Using APOE ε4 as an indicator of high risk, we investigated factors associated with cognitive resilience among black and white older adults who are APOE ε4 carriers. DESIGN, SETTING, AND PARTICIPANTS: Participants included 2487 community-dwelling older (aged 69–80 years at baseline) black and white adults examined at 2 community clinics in the prospective cohort Health, Aging, and Body Composition (Health ABC) study. The baseline visits occurred from May 1997 through June 1998. Our primary analytic cohort consisted of 670 APOE ε4 carriers (329 black and 341 white participants) who were free of cognitive impairment at baseline and underwent repeated cognitive testing during an 11-year follow-up (through 2008) using the Modified Mini-Mental State Examination. MAIN OUTCOMES AND MEASURES: We stratified all analyses by race. Using the Modified Mini-Mental State Examination scores, we assessed normative cognitive change in the entire cohort (n = 2487) and classified the APOE ε4 carriers as being cognitively resilient vs nonresilient by comparing their cognitive trajectories with those of the entire cohort. We then conducted bivariate analyses and multivariable random forest and logistic regression analyses to explore factors predictive of cognitive resilience in APOE ε4 carriers. RESULTS: Among white APOE ε4 carriers, the strongest predictors of cognitive resilience were, in relative order of importance, no recent negative life events, a higher literacy level, advanced age, a higher educational level, and more time spent reading. Among black APOE ε4 carriers, the strongest predictors of cognitive resilience were, in relative order of importance, a higher literacy level, a higher educational level, female sex, and the absence of diabetes mellitus. In follow-up logistic regression models, higher literacy level (adjusted odds ratio [OR], 9.50 [95%CI, 2.67–60.89]), a higher educational level (adjusted OR for college graduate vs less than high school, 3.81 [95%CI, 1.13–17.56]), and age (adjusted OR for 73–76 vs 69–72 years, 2.01 [95%CI, 1.13–3.63]) had significant independent effects in predicting cognitive resilience among white APOE ε4 carriers. Among black APOE ε4 carriers, a higher literacy level (adjusted OR, 2.27 [95%CI, 1.29–4.06]) and a higher educational level (adjusted OR for high school graduate/some college vs less than high school, 2.86 [95%CI, 1.54–5.49]; adjusted OR for college graduate vs less than high school, 2.52 [95%CI, 1.14–5.62]) had significant independent effects in predicting cognitive resilience. CONCLUSIONS AND RELEVANCE: Although APOE ε4 carriers are at high risk for cognitive decline, our findings suggest possible intervention targets, including the enhancement of cognitive reserve and improvement of other psychosocial and health factors, to promote cognitive resilience among black and white APOE ε4 carriers.